Przetwarzanie danych biometrycznych dzieci w związku z korzystaniem ze szkolnej stołówki. Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 10 października 2024 r., III OSK 4804/21 - Kupiec, Mateusz (PRAWO i WIĘŹ, 2025)
The commentary is a critical analysis of the Supreme Administrative Court (NSA) ruling, which found that the processing of students’ biometric data by a school for verifying payments for the use of the school canteen services complies with the requirements of the GDPR. The analysis elaborates in detail on the court’s interpretation of the principle of data minimization, purpose limitation, and the criterion of „freely given” consent. The author points out inaccuracies in the court’s assessment, arguing that the processing of children’s biometric data in this manner constitutes a disproportionate interference with their privacy. The author discusses the court’s reasoning regarding the relationship between the consent of the data subject and the data processing principles outlined in Article 5 of the GDPR. Concerns are also raised about the court’s assessment that the legal guardians’ consent was „freely given”, which, according to the author, fails to sufficiently account for the relationship between the school and students and the potential imbalance of power between the parties.